Microleakage assessment of fissure sealant following fissurotomy bur or pumice prophylaxis use before etching - Ali Bagherian; Majid Akbari; Mohsen Rezaeian; Ghassem Ansari (Wolters Kluwer Medknow Publications, 2013)
Background: A prolonged life of fissure sealant has always been the target for preventing caries in vulnerable newly erupted teeth. The use of preparatory techniques including bur introduction to the fissures is considered among such improving steps. The aim of this investigation was to compare the microleakage level of fissure sealants prepared by a fissurotomy bur or pumice prophylaxis prior to acid etching. Materials and Methods: Ninety freshly extracted healthy maxillary premolar teeth were randomly selected for this investigation. Teeth were then divided into three fissure sealant preparatory groups of A: Fissurotomy bur + acid etch; B: Pumice prophylaxis + acid etch and C: Acid etch alone. Sealant was applied to the occlusal fissures of all specimens using a plastic instrument. This was to avoid any air trap under the sealant. Sample teeth were first thermocycled (1000 cycles, 20 s dwell time) and then coated with two layers of nail varnish leaving 2 mm around the sealant. This was then followed by immersion in basic fuchsin 3%. Processed teeth were sectioned longitudinally and examined under a stereomicroscope for microleakage assessment using a score of 0-3. Collected data was then subjected to Kruskall-Wallis Analysis of Variance and Mann-Whitney U-test. P < 0.05 was considered as significant. Results: Teeth in fissurotomy bur and pumice prophylaxis groups had significantly reduced level of microleakage than those in acid etch alone (P = 0.005 and P = 0.003, respectively). Conclusion: Use of fissurotomy bur and pumice prophylaxis accompanied with acid etching appears to have a more successful reduction of microleakage than acid etch alone.